Study of megakaryocytes in bone marrow aspiration smears in patients with thrombocytopenia - Choudhary, PK; Sing, SK; Basnet, RB (Journal of Pathology of Nepal, 2013)
Background: Dysplastic changes in megakaryocyte are well-recognized features of myelodysplastic syndrome. However, several studies have shown it’s occurrence in various other disorders. This study was done to understand the various megakaryocytic alterations including the dysplastic forms in hematological disorders presenting with thrombocytopenia other than in myelodysplastic syndrome. Materials and Methods: All cases of thrombocytopenia in the study period of May 2010 to April 2012 were included. Bone marrow aspiration study was done in each case of thrombocytopenia. Megakaryocytes were examined in bone marrow aspiration smears in terms of their number and morphology. Dysplasia was considered significant if ≥ 10% of megakaryocyte examined show dysplastic morphology. Results: Dysplastic megakaryocytes were observed in 52.3%, 50% and 21.2% of the cases of megaloblastic anemia, acute leukemia and immune thrombocytopenic purpura respectively. Most common dysplastic feature observed were multiple separate nuclei (25.2%) and micromegakaryocyte (17.3%). Hypogranular form was the least observed dysplastic feature (1.4%; 2/139 cases). Conclusion: Dysplasia in megakaryocyte is a quiet common occurrence in various non-myelodysplastic syndroms related thrombocytopenia. The mere presence of dysplastic megakaryocyte should not prompt an interpretation of myelodysplastic syndroms and should always be correlated with patient’s clinical and other hematological parameters. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8997 Journal of Pathology of Nepal (2013) Vol. 3, 476-481